The Electoral Consequences of Nuclear Fallout: Evidence from Chernobyl - Adrian Mehic (Lund University, School of Economics and Management, Department of Economics, 2020)
What are the political effects of a nuclear accident? Following the 1986 Chernobyl disaster, environmentalist parties were elected to parliaments in several nations. This paper uses Chernobyl as a natural experiment creating variation in radioactive fallout exposure over Sweden. I match municipality-level data on cesium ground contamination with election results for the anti-nuclear Green Party, which was elected to parliament in 1988. After adjusting for pre-Chernobyl views on nuclear power, the results show that voters in high-fallout areas were more likely to vote for the Greens. Additionally, using the exponential decay property of radioactive isotopes, I show a persistent, long-term effect of fallout on the green vote. However, the Chernobyl-related premium in the green vote has decreased substantially since the 1980s. Detailed individual-level survey data further suggests that the results are driven by a gradually decreasing resistance to nuclear energy in fallout-affected municipalities.
Keywords: D72; P16; Q48; Q53; 330; Chernobyl; pollution; voting